Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Giakoumi, Sylvaine; McGowan, Jennifer; Mills, Morena; Beger, Maria; Bustamante, Rodrigo H.; Charles, Anthony; Christie, Patrick; Fox, Matthew; Garcia-Borboroglu, Pablo; Gelcich, Stefan; Guidetti, Paolo; Mackelworth, Peter; et al. (Frontiers in Marine Science, 2018)
Marine protected areas (MPAs) form the cornerstone of marine conservation. Identifying which factors contribute to their success or failure is crucial considering the international conservation targets for 2020 and the limited funds generally available for marine conservation. We identified common factors of success and/or failure of MPA effectiveness using peer-reviewed publications and first-hand expert knowledge for 27 case studies around the world. We found that stakeholder engagement was considered as the most important factor affecting MPA success, and equally, its absence, was the most important factor driving failure. Conversely, while some factors were identified as critical for success, their absence was not considered as a driver of failure, and vice versa. This mismatch provided impetus for considering these factors more critically. Bearing in mind that most MPAs have multiple objectives, including non-biological, this highlights the need for the development and adoption of standardized effectiveness metrics, besides biological considerations, to measure factors contributing to the success or failure of MPAs to reach their objectives. Considering our conclusions, we suggest the development of specific protocols for the assessment of stakeholder engagement, the role of leadership, the capacity of enforcement and compliance with MPAs objectives. Moreover, factors defining the success and failure of MPAs should be assessed not only by technical experts and the relevant authorities, but also by other stakeholder groups whose compliance is critical for the successful functioning of an MPA. Combining these factors with appropriate ecological, social, and economic data should then be incorporated into adaptive management to improve MPA